(untitled) (Medical Forum Monthly, 2021)
Objective: The objective of the study was to determine the absence of Palmaris Longus muscle in patients presenting at Hayatabad medical complex, Peshawar. Study Design: Descriptive Cross Sectional study. Place and Duration of Study: This study was conducted at the Hayatabad Medical Complex, Peshawar for a period of six months from January 2019 to June 2019. Materials and Methods: A total of 432 cases which included male and female both of all ages were included in the study. Schaeffer Test was performed on them to find out the absence of Palmaris longus tendon. Results: Out of 432 subjects, 202 females and 230 males, 70 (16.2%) were found to have absence of Palmaris longus muscle. Out of this 58 (82.8%) were female and 12 (17.1%) were male. Conclusion: The findings of this study highlight the variation in the presence of Palmaris longus muscle.